Can natural fibers be a silver bullet? Antibacterial cellulose fibers through the covalent bonding of silver nanoparticles to electrospun fibers. (11th January 2016) - Zheng, Yingying; Cai, Chao; Zhang, Fuming; Monty, Jonathan; Linhardt, Robert J; Simmons, Trevor J
Abstract: Natural cotton was dissolved in a room-temperature ionic liquid 1-ethyl-3-methyl acetate and wet-jet electrospun to obtain nanoscale cotton fibers with a substantially reduced diameter—and therefore an increased surface area—relative to natural cotton fibers. The resulting nano-cotton fibers were esterified with trityl-3-mercaptopropionic acid, which after selective de-tritylation afforded nano-cotton fibers containing reactive thiol functionality. Silver nanoparticles that were covalently attached to these sulfhydryl groups were assembled next. The microstructure of the resulting nanocomposite was characterized, and the antibacterial activity of the resulting nano-cotton Ag-nanoparticle composite was also studied. This nanocomposite showed significant activity against both Gram-negative and Gram-positive bacteria.